PENGARUH DISIPLIN KERJA DALAM MEMEDIASI HUBUNGAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA - Baginta Fahmi Subastian (JURNAL CAFETARIA, 2022)
This study aims to see the influence of work discipline in mediating the relationship between the work environment and employee job satisfaction at the Yogyakarta Regional Financial and Asset Management Agency. The number of respondents used as a sample in this study was as many as 70 civil servants. The results showed that: (1) The work environment has a positive and significant effect on work discipline at the Yogyakarta Regional Financial and Asset Management Agency, as can be seen from the t values of 184,194, (2) The work environment has a positive and significant effect on employee job satisfaction at the Yogyakarta Regional Financial and Asset Management Agency with a t values of 21,699, (3) Work discipline has a positive and significant effect on employee job satisfaction in the Agency Yogyakarta Regional Financial and Asset Management with a value of 6,480, (4) The work environment has a positive and significant effect on employee job satisfaction at the Yogyakarta Regional Financial and Asset Management Agency which is mediated by work discipline with a value of 190,674.